The effect of Pilates-Assisted acceptance and commitment therapy (ACT)-based mindfulness training on the self-esteem and social functioning of individuals diagnosed with substance use disorder - Ersöğütçü, Filiz; Ekinci, Mine (Journal of Dependence, 2026)
Objective: This study aimed to examine the association between Pilates-assisted Acceptance and Commitment Therapy (ACT)-based mindfulness training and changes in social functioning and self-esteem among individuals diagnosed with substance use disorder (SUD). Methods: A quasi-experimental pre-test, post-test, and follow-up design with experimental and control groups was employed. The study was conducted between September 1, 2018, and November 22, 2019, at an inpatient Alcohol and Substance Addiction Treatment Center (AMATEM). Seventy-nine inpatients with SUD participated. The experimental group received 12 Pilates sessions and 9 ACT-based mindfulness sessions in addition to routine treatment. Social functioning was assessed using the Social Functioning Scale (SFS), and self-esteem was measured using the Coopersmith Self-Esteem Inventory (CSEI). Effect sizes were calculated using partial eta-squared (η²p) and Cohen’s d. Results: Social functioning scores increased over time in both groups. However, the group × time interaction was not statistically significant for total SFS scores (p = .758, partial η² = .001) or CSEI scores (p = .571, partial η² = .004). A significant main effect of time was observed for social functioning (p < .001, partial η² = .267). At the three-month follow-up, the between-group difference in total SFS scores corresponded to a moderate effect size (Cohen’s d = 0.50), whereas the effect size for self-esteem was negligible (Cohen’s d = 0.05). Conclusion: Participation in the Pilates-assisted ACT-based mindfulness program was associated with improvements in social functioning within an inpatient addiction treatment setting. Although longitudinal group differences were not statistically significant, the moderate effect size observed at ...